5-fluorocitosina e anfotericina-B no tratamento da criptococose do sistema nervoso central Amphotericin-B and 5-fluorocytosine in the treatment of cryptococcosis of the central nervous system: report of two cases - J. P. S. Nobrega; J. A. Livramento; A. Spina-França (Arquivos de Neuro-Psiquiatria)
Registro de dois casos de criptococose do sistema nervoso central, em um deles associada a candidíase. Em ambos foram utilizados no tratamento anfotericina-B e 5-fluorocitosina. Em função dos resultados obtidos são feitas considerações quanto à utilidade de cada uma das drogas no tratamento da criptococose, bem como quanto ao uso associado de ambas. Two cases of cryptococcosis of the central nervous system are reported. The treatment was based on the association of amphotericin-B with 5-fluorocytosine. Details on the therapeutic proprieties of these drugs are discussed considering the results obtained. Amphotericin-B was administered intravenously and intrathecally in the two cases. The total amount of amphotericin administered intravenously in the first case was 5.375 mgm, and the oral doses of 5-fluorocytosine were not superior to 100 mgm/kg/of body weight. This patient died 130 days after the first symptoms of the disease. The second patient had been submitted previously to kidney transplantation after bilateral nephrectomy, and inmunossupressive drugs were administered to him since then. Candidiasis and cryptococcosis of the central nervous system developped two years later. 5-fluorocytosine was administered orally (200 mgm/kg of body weight) and amphotericin-B. The total amount of this drug administered intravenously was 2.00 mgm. There was complete clinical and laboratory remission of the mycoses in this case.